The Analysis of Effectivity and Efficiency of Tax Collection from Hotels and Restaurants in Order to Increase The Original Regional Income (PAD) in Mataram - Rini Yuliandari; Taufik Chaidir; Hadi Mahmudi (Universitas Negeri Malang, 2017)
This research aims to discover the effectivity, the efficiency, the performance as well as the contribution of tax collection from hotels and restaurants toward the Original Regional Income in Mataram from 2011 until 2016. The method used is a quantitative method for case study as the data collection. The result shows that the effectivity and efficiency of the tax collection from hotels and restaurants in Mataram are considered in the effective and efficient category. Meanwhile, the contribution of hotels and restaurants tax collection to the regional tax is 0,27% and 0,13% toward the Original Regional Income, thus, the hotel and restaurant taxes give a good contribution to the regional tax and original regional income in Mataram. In addition, the performance of hotels and restaurants tax is in a developing category.Keywords: Effectivity, Efficiency, Performance, Hotel and Restaurant Tax, Original Regional Income (PAD)JEL Classification: G31, H17